2014
DOI: 10.1074/jbc.m114.585653
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ethanol Consumption Inhibits Glucokinase Transcriptional Activity by Atf3 and Triggers Metabolic Syndrome in Vivo

Abstract: Background: Chronic ethanol consumption induces pancreatic β-cell dysfunction and metabolic syndrome.Results: Ethanol-induced Atf3 inhibits glucokinase transcriptional activity through direct binding or Atf3/Pdx-1/Hdac1 axis on glucokinase promoter.Conclusion: ATf3 fosters β-cell dysfunction via Gck down-regulation and triggers T2D, which is ameliorated by in vivo Atf3 silencing.Significance: The presented data uncover a new role for Atf3 as a potential therapeutic target in treating type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 39 publications
4
29
1
Order By: Relevance
“…This result resembled those from previous laboratory studies . Although several short‐term RCTs with small sample sizes found that moderate alcohol consumption in females improved insulin sensitivity , more research demonstrated that chronic alcohol intake can lead to whole‐body insulin resistance . In contrast, the effects of alcohol on insulin secretion were inconsistent among previous studies .…”
Section: Discussioncontrasting
confidence: 81%
“…This result resembled those from previous laboratory studies . Although several short‐term RCTs with small sample sizes found that moderate alcohol consumption in females improved insulin sensitivity , more research demonstrated that chronic alcohol intake can lead to whole‐body insulin resistance . In contrast, the effects of alcohol on insulin secretion were inconsistent among previous studies .…”
Section: Discussioncontrasting
confidence: 81%
“…9F) compared to those in niltubacin-treated BK-SS mice. Although we were limited regarding isolation of various cellular subpopulations from drug-treated lungs, it was likely that decreased ET-1 levels arose predominantly from pulmonary endothelial cells, as previously shown (21). Taken together, these data showed that tubacin, a selective inhibitor of histone deacetylase 6 (HDAC6), attenuated ET-1 and PlGF levels in BK-SS mice by upregulating DNM3os/miR-199a2/miR-214 transcription.…”
Section: Binding Of Atf3 Jdp2 and Hdac6 To The Dnm3os Promoter As Dsupporting
confidence: 58%
“…The ATF3 gene, a stress-inducible gene, has been shown to play important roles in several pathological conditions, including host immunity and cancer (19)(20)(21). To de-at Cincinnati Children's Hospital Medical Center.…”
mentioning
confidence: 99%
“…C). Among them, four considerations prompted us to target ATF3 as the downstream candidate of IRF2BP2: (1) The binding of IRF2BP2 on the ATF3 gene has the highest binding peak score and is in close proximity to the transcription start site (−140 bp); (2) multiple lines of evidences have suggested a pathogenic role of ATF3 in NAFLD and insulin resistance; (3) current understanding indicates a strong preference for IRF2BP2 as a transcription repressor; and (4) ATF3 expression was increased in IRF2BP2 ‐KO cells. Indeed, the up‐regulation of ATF3 mRNA levels in hepatosteatosis models, both in vitro and in vivo , were profoundly reinforced by Irf2bp2 depletion but were conversely suppressed by Irf2bp2 overexpression, as verified by real‐time PCR examinations (Fig.…”
Section: Resultsmentioning
confidence: 99%